MANAGEMENT CONSULTANCY AND CORPORATE EFFECTIVENESS IN SMALL SCALE ENTREPRENEURIAL FIRMS IN OKIGWE (Journal of the Management Sciences, 2024)
Many businesses suffer corporate ineffectiveness because of their perceived poor attitude to management consultancy services hence this study on management consultancy and corporate effectiveness in small scale entrepreneurial firms in Okigwe. The study examines the relationship between management consultancy and employee commitment; and it evaluates the level of correlation between management consultancy and customer loyalty in small scale entrepreneurial firms in Okigwe. Two research questions and two hypotheses guide the study. The research employs the survey research design. It uses a five-point Likert Scale structured questionnaire as the major instrument for data collection. The study employs the Cronbach Alpha statistic for obtaining 0.86 as the reliability ratio of the survey instrument. The study commits data analysis to descriptive statistics of mean score and standard deviations. It uses correlation analysis for testing hypotheses. The study finds that there is a significant relationship between management consultancy and employee commitment; and there is a significant level of correlation between management consultancy and customer loyalty in small scale entrepreneurial firms in Okigwe. The study concludes that management consultancy correlates with corporate effectiveness in small scale entrepreneurial firms in Okigwe. The study recommends that small scale entrepreneurial firms need to enhance the rate at which they embrace management consultancy so as to always increase employee commitment and customer loyalty. Also, employees in small scale entrepreneurial firms need to make more efforts to support management in the efforts it makes to improve overall effectiveness of the enterprises.
Keywords: Management consultancy, Employee commitment, Customer loyalty, Small scale entrepreneurial firms